2024
DOI: 10.14712/fb2024070010062
|View full text |Cite
|
Sign up to set email alerts
|

Parallel DNA/RNA NGS Using an Identical Target Enrichment Panel in the Analysis of Hereditary Cancer Predisposition

Petra Kleiblová,
Marta Černá,
Petra Zemánková
et al.

Abstract: Germline DNA testing using the next-gene­ration sequencing (NGS) technology has become the analytical standard for the diagnostics of hereditary diseases, including cancer. Its increasing use places high demands on correct sample identification, independent confirmation of prioritized variants, and their functional and clinical interpretation. To streamline these processes, we introduced parallel DNA and RNA capture-based NGS using identical capture panel CZECANCA, which is routinely used for DNA analysis of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…Interestingly, CHEK2 GPV identified in 6/123 (4.9%) early-onset OC patients were significantly associated with earlier age at diagnosis compared to previously analyzed OC patients negative for GPV in HBOP cancer predisposition genes 6 . It is noteworthy that one CHEK2 deep intronic variant was identified only by RNA NGS which underlines the importance of RNA analysis 47 . Furthermore, GPV in CHEK2 have been identified in early-onset OC patients by other studies 6 , 10 , 48 , 49 , the most prevalently by Carter et al 10 who identified CHEK2 GPV in 5/147 (3.4%) early-onset OC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, CHEK2 GPV identified in 6/123 (4.9%) early-onset OC patients were significantly associated with earlier age at diagnosis compared to previously analyzed OC patients negative for GPV in HBOP cancer predisposition genes 6 . It is noteworthy that one CHEK2 deep intronic variant was identified only by RNA NGS which underlines the importance of RNA analysis 47 . Furthermore, GPV in CHEK2 have been identified in early-onset OC patients by other studies 6 , 10 , 48 , 49 , the most prevalently by Carter et al 10 who identified CHEK2 GPV in 5/147 (3.4%) early-onset OC patients.…”
Section: Discussionmentioning
confidence: 99%